A decade of experience evolving visiting dental services in partnership with rural remote Aboriginal communities. (June 2014) - Dyson, K; Kruger, E; Tennant, M
Abstract Background Embedding research capabilities and workforce development activities with clinical service entities promotes the development of sustainable, innovative, quality‐focused oral health care services. Clinical and strategic governance is an important area of consideration for rural and remote dental services, posing particular challenges for smaller service structures. Sustaining remote area dental services has some significant complexities beyond those involved in urban service models. Methods This study describes the sustaining structure of a remote area dental service with a decade of history. Results In the current climate, chief among these challenges may be those associated with dental workforce shortages as these impact most heavily in the public sector, and most particularly, in remote areas. As sustained workforce solutions come from developing a future workforce, an essential element of the workforce governance framework for remote dental service provision should be the inclusion of a student participation programme. Collaborative partnership approaches with Aboriginal health services promote the development and maintenance of effective, culturally sensitive dental services within rural and remote Aboriginal communities. Having sustained care for 10 years, this collaborative model of integrated research, education and service has demonstrated its effectiveness as a service model for Aboriginal communities in Western Australia. Conclusions This descriptive study finds the core values for this success have been communication, clinical leadership, mentorship within effective governance systems all linked to an integrated education and research agenda.